If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35 + -3x = 14 + -10x Solving 35 + -3x = 14 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 35 + -3x + 10x = 14 + -10x + 10x Combine like terms: -3x + 10x = 7x 35 + 7x = 14 + -10x + 10x Combine like terms: -10x + 10x = 0 35 + 7x = 14 + 0 35 + 7x = 14 Add '-35' to each side of the equation. 35 + -35 + 7x = 14 + -35 Combine like terms: 35 + -35 = 0 0 + 7x = 14 + -35 7x = 14 + -35 Combine like terms: 14 + -35 = -21 7x = -21 Divide each side by '7'. x = -3 Simplifying x = -3
| 3x-24=4x-8 | | 1-3x(1)-(-3)-2(x-3)=3x-(-4) | | 2x+7=6x+19 | | (8x-64x^(-1/2)) | | -(8v-7)=25-5v | | -7f=56 | | (7x+1)(8x-6)= | | x+7=3x+9.5 | | (x^(2/3)y^(-(5/4)))^6 | | 1.4/7.7 | | lg(x^2-x-6)-lg(x-3)=0 | | 25x^2+35x=0 | | 5=-7+a | | 40=-8(x+2) | | 1.5y-2=y | | 1/2x+2/5=1/3x+3/4 | | 10*t+6*(0.8-t)=6 | | (x-16)2=64 | | 9x+20=2x+125 | | 4x-6=x-18 | | -5k-2+9k+6= | | 1/2(6x-4)-4x=3x-18 | | x^4+18x^2+17=0 | | 3x-x+1=2x+5 | | 7=n+5 | | x*x+25=10x | | 9n+7n-5-4= | | 4x-5y+3z= | | .75(4-8x)=0.8(5+10x)+1 | | a(3a-2)+2a(a+4)=a(a+2) | | Ln(x-15)=10 | | 4x-6-3x= |